2007
DOI: 10.1590/s1516-89132007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to leaf rust in coffee carrying S H3 gene and others S H genes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 1 publication
0
9
0
3
Order By: Relevance
“…Race II, which was introduced into Brazil and other Latin American countries possesses only one of the nine known virulence factors, v 5 . Over time, races of increasing complexity, involving eight virulence factors in different combinations, have progressively appeared in Brazil (Sera et al 2007;Cabral et al 2009) and Colombia (Alvarado-Alvarado and Moreno-Ruiz 2005). Conversely, the evolution of coffee rust in Central America has apparently been slow.…”
Section: The Question Of New Racesmentioning
confidence: 99%
“…Race II, which was introduced into Brazil and other Latin American countries possesses only one of the nine known virulence factors, v 5 . Over time, races of increasing complexity, involving eight virulence factors in different combinations, have progressively appeared in Brazil (Sera et al 2007;Cabral et al 2009) and Colombia (Alvarado-Alvarado and Moreno-Ruiz 2005). Conversely, the evolution of coffee rust in Central America has apparently been slow.…”
Section: The Question Of New Racesmentioning
confidence: 99%
“…reported that "Catucai" lines are attacked by rust at different levels, but several do not lose leaves sharply and chemical control is easy using copper fungicides. 1,016 d 1,000 e Paraíso H-419-10-6-2-5-1 1,000 d 1,000 e Paraíso H-419-10-6-2-10-1 1,000 d 1,000 e 'IPR 100' was originated from a crossing between "Catuaí" and one hybrid ("Catuaí" x series BA-10 coffee) carrying Coffea liberica genes, but it was probably not a carrier of the SH3 gene, because in Londrina coffee trees with this gene were completely resistant to the rust (Sera et al 2007a(Sera et al , 2010b. 'IPR 100' is resistant to race II (gene v5) of H. vastatrix, while the cultivars from the "Catuaí" germplasm, carriers only of SH5, are susceptible (Capucho et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In another study in Londrina, it was observed that the SH1, SH2, SH4, SH5 and SH8 genes had already been broken by the local population of rust races. Furthermore, it was observed that coffee tree carriers of SH3, Hibrido de Timor CIFC 832/1 and CIFC 832/2 had complete resistance (Sera et al 2007a). It could be probable that these cultivars that presented complete resistance at two locations were the carriers of the SH5, SH6, SH7, SH8 and SH9 genes and other resistance genes to rust in different combinations.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, complete rust resistance has been observed in coffee carrying SH3 (Conceição et al 2005, Pereira et al 2005, Sera et al 2007a, Sera et al 2010a). …”
Section: Grade Descriptionmentioning
confidence: 98%
“…Race III (v1, v5) was detected in the States of São Paulo, Espírito Santo, Minas Gerais, and Paraná and race XV (v4,v5) in the states of São Paulo, Espírito Santo and Minas Gerais. Complex races, such as XVI (v1,v2,v3,v4,v5) with several virulence genes, were identified only in coffee germplasm with complex combinations of resistance v2, v4, v5, and v8, alone or in combinations (Sera et al 2007a). …”
Section: Grade Descriptionmentioning
confidence: 99%